Determination of Lead in Drinking and Wastewater by Hydride Generation Atomic Absorption Spectrometry. (12th August 2016) - Bakırdere, Sezgin; Chormey, Dotse Selali; Büyükpınar, Çağdaş; San, Nevim; Keyf, Seyfullah
ABSTRACT: This work describes the optimization of hydride generation atomic absorption spectrometry for the determination of lead at trace concentrations. The parameters affecting the production, transport, and atomization of plumbane in a closed vessel were optimized. The concentrations of reagents affecting the generation of the lead hydride were also optimized to obtain high hydride generation efficiency. The atomization temperature, reaction period, pump speed, pump period, and flow rates of reducing agent and carrier gas were varied to maximize the sensitivity for lead. The accuracy of the method was evaluated by the analysis of certified reference materials. The method provided a linear dynamic range for lead from 2.0 to 40 µg/L with a limit of detection of 0.56 µg/L.